Mechanical properties of the poly(vinyl alcohol) based nanocomposites at low content of surfactant wrapped graphene sheets. (9th March 2015) - Moradi, Mina; Mohandesi, Jamshid Aghazadeh; Haghshenas, Davoud Fatmehsari
Abstract: One necessary point towards achieving the enhanced mechanical properties in the nanocomposite systems, comprising a polymeric matrix and the graphene sheets (GSs) as the reinforcement, is the number of GSs layers regarding its relation with the gyration radius of the matrix. In this study, a stable suspension containing the surfactant wrapped graphene sheets (SWGSs) was successfully synthesized via a facile electrochemical route in the sodium dodecyl sulfate media. The effect of the applied potential was qualified and quantified during preparation of SWGSs by employing X-ray diffraction, chronoamperometry and Raman spectroscopy. It was found that an increase in the level of applied potential from 5 to 15 V improves the production yield of SWGSs (≈56%). The prepared SWGSs, which contained monolayer as well as multilayer sheets, were then dispersed in the Poly(Vinyl Alcohol) (PVA) matrix through liquid blending method. It was observed that the tensile strength and Young's modulus of the fabricated nanocomposite (PVA/SWGSs) increase even at low level GSs content. Furthermore, the effect of temperature on the fabrication process of the nanocomposites was evaluated via thermal analysis. Graphical abstract: Highlights: Surfactant wrapped graphene sheet (SWGS) was synthesized via an electrochemical way. The high quality product is a mixture of mono and multilayer of graphene sheets. Poly(vinyl alcohol) (PVA)/SWGSs nanocomposite was produced via liquid blending path. Mechanical properties of the PVA/SWGSs nanocomposite increase at low GSs loading. Temperature of the making process has an effect on the nanocomposite's behavior.